THE ASSESSMENT OF TRANSLATION QUALITY IN BOUND NOVEL - Rahayu . Ningsih; Anni Holila Pulungan; Zainuddin . . (LINGUISTIK TERAPAN, 2021)
The objectives of this study were to describe the translation quality in Bound novel. This study followed the theory of Nababan et.al (2012) about the three aspects of translation quality namely (1) accuracy; (2) acceptability; and (3) readability. This research uses descriptive qualitative method as the research design. The data of this study were gathered by using the documents and questionnaire by the raters. The results analysis from the raters showed that translation quality in Bound novel were less accurate with the average points around 2.75, acceptable with the average points around 2.92 and readable with the average points around 3.0. It means, the quality of translation in Bound novel was good quality. Keywords: Translation Quality, Bound Novel . Assessment, Aspects of Translation